Treatment of Essential Tremor with Long-Chain Alcohols: Still Experimental or Ready for Prime Time?. (5th February 2014) - Haubenberger, Dietrich; Nahab, Fatta B.; Voller, Bernhard; Hallett, Mark
Aim: To review current literature on long-chain alcohols and their derivatives as novel pharmacotherapy for the treatment of essential tremor (ET). Background: Currently available and recommended pharmacotherapies for ET are often limited by suboptimal treatment effects, frequent adverse effects, and drug interactions. While ethanol is reported to profoundly decrease tremor severity in the majority of patients with ET, preclinical experience suggests that long-chain alcohols such as 1-octanol might lead to a comparable tremor reduction without ethanol's typical side effects of sedation and intoxication. Here, we review the literature on the first clinical trials on 1-octanol and its metabolite octanoic acid (OA) for the treatment of ET. Methods: The literature on preclinical and clinical trials on long-chain alcohols as well as OA was reviewed and summarized, and an outlook given on next phases of development. Discussion: 1-octanol was demonstrated to be safe and effective in a double-blind, placebo-controlled low-dose trial, and open-label data showed excellent tolerability and dose-dependent efficacy up to 128 mg/kg. Despite 1-octanol's efficacy, its future viability as an effective therapy is limited by its pharmacological properties that require large volumes to be orally administered. Pharmacokinetic data indicate that OA is the active metabolite of 1-octanol. Preclinical efficacy data for OA are positive, and human pilot data demonstrated excellent safety as well as efficacy in secondary outcome measures of tremor amplitudes. OA also has more favorable pharmacological properties for drug delivery; hence, OA may be worth developing as a pharmaceutical.